Reading comprehension: a viable challenge for public school students (2000)
This study was conducted in the Diana Turbay state school with students of one eighth grade class with a low English level. The group was chosen because of their special characteristics within this public institution: their number (just eighteen students) and their interest in and motivation for learning English as a foreign language. The motivation they show allowed the researchers to observe and collect more specific information for this study and for future research on reading comprehension. Data collection was conducted using many different techniques, such as open observations, diary, surveys, students’ self-evaluation and field notes. All these techniques provided information as authentic as possible. The purpose of the study was to determine if students improved their reading comprehension in English by applying specific reading strategies. Results showed that students from state schools can achieve good comprehension of English texts through adequate training despite the fact that they start their English learning so late. Further research on this topic should study the relationship between reading comprehension in Spanish and in English. It would also be necessary to study how students can acquire language structures through reading activities.